2019
DOI: 10.1017/aog.2019.37
|View full text |Cite
|
Sign up to set email alerts
|

CReSIS airborne radars and platforms for ice and snow sounding

Abstract: This paper provides an update and overview of the Center for Remote Sensing of Ice Sheets (CReSIS) radars and platforms, including representative results from these systems. CReSIS radar systems operate over a frequency range of 14-38 GHz. Each radar system's specific frequency band is driven by the required depth of signal penetration, measurement resolution, allocated frequency spectra, and antenna operating frequencies (often influenced by aircraft integration). We also highlight recent system advancements … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

5
2

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 29 publications
2
33
0
Order By: Relevance
“…Rodriguez-Morales and others, 2013; Kjær and others, 2018). Ultimately, new platforms, such as rovers, drones and satellites stand to transform the way radar-sounding observations are made (Jezek and others, 2006; Koh and others, 2010; Arcone and others, 2016; Freeman and others, 2017; Dall and others, 2018; Carrer and others, 2018; Gogineni and others, 2018; Culberg and Schroeder, 2019; Arnold and others, 2020).…”
Section: Datamentioning
confidence: 99%
“…Rodriguez-Morales and others, 2013; Kjær and others, 2018). Ultimately, new platforms, such as rovers, drones and satellites stand to transform the way radar-sounding observations are made (Jezek and others, 2006; Koh and others, 2010; Arcone and others, 2016; Freeman and others, 2017; Dall and others, 2018; Carrer and others, 2018; Gogineni and others, 2018; Culberg and Schroeder, 2019; Arnold and others, 2020).…”
Section: Datamentioning
confidence: 99%
“…2), although a ≤ 30 MHz system is a more conservative suggestion. For thicker glaciers in Alaska, Iceland and the southern Andes, a lower-frequency (≤ 30 MHz) radar sounder remains necessary for many glaciers, and ≤ 10 MHz may be more suitable, as observed in practice (e.g., Conway et al, 2009;Björnsson and Pálsson, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Their analysis favored center frequencies ≤∼ 10 MHz to increase the signal-to-clutter ratio between the ice-bed reflection (signal) and any cavity-induced volume scattering (clutter). Their lucid description of this challenge motivated the development of numerous low-frequency radar sounders (e.g., Watts and Wright, 1981;Fountain and Jacobel, 1997;Conway et al, 2009;Mingo and Flowers, 2010;Rignot et al, 2013;Arnold et al, 2018;Björnsson and Pálsson, 2020). However, subsequent advances in available hardware, system design and processing demonstrated that higher-frequency (> 10 MHz) radar sounders can also sound hundreds of meters of temperate ice (e.g., Rutishauser et al, 2016;Langhammer et al, 2019;Pritchard et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Our synthesis suggests a higher upper limit (~30 MHz) on potentially suitable radar sounders for sounding temperate ice up to ~700 m thick. Recent advances in hardware and system design could further increase that range, e.g., solid-state transmit/receive switches, higher peak-transmit powers and platformaware numerical optimization of antenna configurations (Arnold et al, 2020).…”
Section: Discussionmentioning
confidence: 99%